Netrin-1 expression is an independent prognostic factor for poor patient survival in brain metastases - Harter, Patrick Nikolaus; Zinke, Jenny; Scholz, Alexander; Tichy, Julia Frederike; Zachskorn, Cornelia; Kvasnicka, Hans M.; Goeppert, Benjamin; Delloye-Bourgeois, Céline; Hattingen, Elke; Senft, Christian; Steinbach, Joachim Peter; Plate, Karl; et al. (PLOS ONE, 2014)
The multifunctional molecule netrin-1 is upregulated in various malignancies and has recently been presented as a major general player in tumorigenesis leading to tumor progression and maintenance in various animal models. However, there is still a lack of clinico-epidemiological data related to netrin-1 expression. Therefore, the aim of our study was to elucidate the association of netrin-1 expression and patient survival in brain metastases since those constitute one of the most limiting factors for patient prognosis.